Quality of life improves after palliative placement of percutaneous tunneled drainage catheter for refractory ascites in prospective study of patients with end-stage cancer. Issue 6 (December 2019) - Robson, Piera Cote; Gonen, Mithat; Ni, Ai; Brody, Lynn; Brown, Karen T.; Getrajdman, George; Thom, Bridgette; Kline, Nancy; Covey, Anne
Abstract: Objective: Percutaneous tunneled drainage catheter (PTDC) placement is a palliative alternative to serial paracenteses in patients with end-stage cancer and refractory ascites. The impact of PTDC on quality of life (QoL) and long-term outcomes has not been prospectively described. The objective was to evaluate changes in QoL after PTDC. Method: Eligible adult patients with end-stage cancer undergoing PTDC placement for refractory ascites completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire and McGill Quality of Life instruments before PTDC placement and at 2 to 7 days and 2 to 4 weeks after PTDC. Catheter function, complications, and laboratory values were assessed. Analysis of QoL data was evaluated with a stratified Wilcoxon signed-rank test. Result: Fifty patients enrolled. Survey completion ranged from 65% to 100% (median 88%) across timepoints. All patients had a Tenckhoff catheter, with 98% technical success. Median survival after PTDC was 38 days (95% confidence interval = 32, 57 days). European Organization for Research and Treatment of Cancer scores showed improvement in global QoL ( p = 0.03) at 1 week postprocedure (PP). Significant symptom improvement was reported for fatigue, nausea/vomiting, pain, dyspnea, insomnia, and appetite at 1 week PP and was sustained at 3 weeks PP for dyspnea ( p < 0.01), insomnia ( p < 0.01), and appetite loss ( p = 0.03). McGill Quality of Life demonstrated overall QoL improvement at 1 ( p = 0.03) and 3 weeks ( p = 0.04) PP. Decline in sodium and albumin values pre- and post-PTDC slowed significantly (albumin slope –0.43 to –0.26, p = 0.055; sodium slope –2.50 to 1.31, p = 0.04). Creatinine values increased at an accelerated pace post-PTDC (0.040 to 0.21, p < 0.01). Thirty-eight catheter-related complications occurred in 24 of 45 patients (53%). Significance of results: QoL and symptoms improved after PTDC placement for refractory ascites in patients with end-stage malignancy. Decline in sodium and albumin values slowed postplacement. This study supports the use of a PTDC for palliation of refractory ascites in cancer patients.